Application of Social Cognitive Theory for Tertiary Preventive Behavior in Elderly with Hypertension: A Multilevel Analysis in Cirebon, West Java - Sita Rahayu Sanusi; Bhisma Murti; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Hypertension is the first non-communicable disease diagnosed in various health facilities up to 185,857 cases. Hypertension is one of the main causes of mortality and morbidity in Indonesia, so the management of this disease is a very common intervention carried out at various levels of health facilities, especially in the elderly. This study aims to analyze the influence of the application of social cognitive theory on the preventive behavior of the elderly tertiary with hypertension in Cirebon Regency. Subjects and Method: The study was conducted with a cross-sectional study design involving as many as 200 research subjects, including 102 positive tertiary preventive behavior research subjects and 93 negative tertiary preventive behavior research subjects. This research was conducted in 25 elderly posyandu in Cirebon Regency, West Java. This research was conducted in March-April 2024. The sample was selected using simple random sampling to select elderly research subjects with hypertension and stratified random sampling to select the type of Posyandu. The dependent variable is tertiary preventive behavior behavior in the elderly with hypertension. The independent variables were knowledge, expectations, self-regulation, self-efficacy, reinforcement and observational learning. Data collection was carried out using questionnaires and data were analyzed using a multilevel analysis model.. Results: Tertiary preventive behavior in older age with hypertension was influenced by knowledge (b = 1.89; 95% CI = 1.54 to 2.23; p <0.001), expectations (b = 0.15; 95% CI = 0.01 to 0.29; p = 0.031), self-regulation (b = 0.15; 95% CI = 0.01 to 0.29; p = 0.035), self-efficacy (b = 0.14; 95% CI = 0.00 to 0.29; p = 0.042), reinforcement (b = 0.15; 95% CI = 0.00 to 0.29; p = 0.042), reinforcement (b = 0.36; 95% CI = 0.22 to 0.50; p <0.001), and observational (b = 0.22; 95% CI = 0.07 to 0.38; p = 0.004). Posyandu has a contextual influence on tertiary preventive behavior in the elderly with hypertension with ICC = 40%. Conclusion: Tertiary preventive behavior in the elderly with hypertension is influenced by knowledge, expectations, self-regulation, self-efficacy, reinforcement and positive outcomes of observational learning. Thus, social cognitive theory can be used to explain and predict tertiary preventive behavior in the elderly with hypertension. Variations at the Posyandu level have a strong contextual effect on tertiary preventive behavior in the elderly with hypertension.